Association Of Term Neonatal Fits With Serum Calcium Levels - Sania Sabir; Mahnoor Javed; Seema Kanwal (Journal of Rawalpindi Medical College, 2019)
Background: The most prominent feature of neurological dysfunction in neonatal period is the occurrence of seizures. Determining its underlying aetiology is critical. The objective of our study was to determine association between low calcium levels and neonatal seizures in cases presenting in Pediatrics Department Holy Family Hospital, Rawalpindi. Methods: This case control study was conducted in Department Of Pediatrics Holy family Hospital Rawalpindi from February 2015 to December 2015 and included 48 neonates including 24 cases of fits and 24 controls with exclusion criteria of prematurity and those born via caesarian section. Data was collected through structured questionnaire. All the data was entered and analyzed by SPSS version 17. Results: Our study comprised of 48 neonates with mean age of 7.7 ±8.1 days. Out of total 29 (60.4%) were male neonates while 19 (39.6%) were females. Among cases 46.2% had hypocalcemia while 53.8% had normocalcemia. Among controls 53.9% had hypocalcemia while 46.1% had normocalcemia. The Odd’s ratio was computed to be 0.714 with confidence interval of 0.228 to 2.233 which shows association is insignificant. Conclusion: Neonatal fits at term were not found to be associated with reduced calcium levels thereby other metabolic abnormalities like hypoglycemia, hyponatremia should be ruled out prior to assessment of serum calcium levels in term neonatal fits.